BIRD DIVERSITY IN AN AGROFORESTRY SYSTEM IN VERACRUZ, MEXICO - FERNÁNDEZ-POPO, MACARIO; CANCHÉ, JUAN M. PECH; ACOSTA, PATRICIA CERVANTES; FUENTES, JORGE LUIS CHAGOYA; MANCERA, BELISARIO DOMÍNGUEZ; BELTRÁN, ANTONIO HERNÁNDEZ (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
The present study investigated the variety and abundance of migratory and resident birds in the confined agroforestry system of an educational farm, from July-October 2019, identifying each specimen with a metal band. With the aid of Howell & Webb’s specialized guide for birds of México and Northern Central America, a presence/absence analysis was carried out, along with first-order Chao 2, Chao 1, ICE and Jackknife species richness estimators; the difference between months observed was represented by a species accumulation curve, and data was evaluated with the Estimates (V.9.1) software. 540 specimens from 66 species, 44 genera, 19 familiae, and 6 orders were captured. The family Parulidae was the most abundant, as was the order Passeriformes; the greatest presence of species was recorded in September and October, with a predominance of 5 specific species. There were 15 recaptures of individuals from 11 species; one was recognized as endemic, 26 migratory species, 1 summer migratory species, 13 transient species, 24 resident species, and 2 species outside their normal distribution area. 3 species are listed in the NOM-059-SEMARNAT-2010 standard, two are classified as “Subject to special protection” (Pr): Limnothlypis swainsonii and Passerina ciris, and one is classified as “Endangered” (A): Geothlypis tolmiei. Two of the represented bird species, Bubulcus ibis and Fulica americana, have been reported as carriers of the West Nile virus, a pathogen that has been recognized as the origin of a zoonosis that affects house animals and humans.